The influence of large class size on English teachers’ performance at “Margarita Cortés,” “María Auxiliadora,” and “Francés” educational institutions in Esmeraldas, 2016 - Ante Boboy, Maricela Mabel (2018)
Tesis previa obtención del título de Licenciado/a en Lingüística Aplicada mención Inglés